Redesign Facility Layout and Minimize Material Handling Cost on PT ABC in Pandemic Era - Oktalia, Riska Dwi; Nafiah, Siti Inaratul; Priska, Hersa Ajeng; Fariza, Rahma (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Since March 2020 the news of Covid-19 has spread in Indonesia, with this situation there have been many changes in the industrial sector in Indonesia. In this situation, industry players should make adjustments to their production processes so they can continue and run safely. According to information from the Ministry of Health and the Task Force for the Acceleration of Handling Covid-19, one of the health protocols to prevent the spread of Covid-19 is physical distancing, where the minimum distance between workers is 1 meter. So to deal with this condition, of course, it is necessary to redesign the layout of the factory facilities. Layout is an important decision that determines the efficiency of long-term operations. PT ABC is a company engaged in the processing of metal goods. In addition to implementing health protocols, PT ABC also has problems in structuring work facilities that are not quite right. This can lead to less effective and efficient workers for moving the material, thus causing a lot of work in process. The analysis method to these problems uses the ARC (Activity Relationship Chart), ARD (Activity Relationship Diagram), and Flexsim 6.0 simulation method to determine the Material Handling Cost and production output. Layout changes that have been made, can minimize material handling costs which were previously $ 28,847.16 reduced to $ 22,717.76 to get $ 6129.4 or about 21%.